2017
DOI: 10.1590/1519-6984.173578
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behavior and at-sea distribution of White-Tailed Tropicbirds in tropical ocean

Abstract: We used miniaturized GPS loggers and site observations to access foraging patterns and nest behaviour of the White-tailed Tropicbird Phaethon lepturus (WTTB), an endangered species at its South Atlantic breeding colony. Dual foraging pattern was observed with alternation between long and short foraging trips. Birds responsible for nest attendance engaged in short foraging trips with mean distance from colony of 25 ± 17 km, total distance covered of 79 ± 65 km and mean duration of 4.02 ± 5.28 hours. Birds flew … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Among these, pelagic species such as tropicbirds, noddies and terns display different foraging modes. White‐tailed tropicbirds mainly forage solitary (Jaquemet et al , Campos et al ), and occasionally associate with feeding dolphins (Jaquemet et al , Spear and Ainley ). Comparatively, sooty terns, brown and black noddies are highly gregarious and are often found in multi‐specific feeding assemblages (Evans , Au and Pitman , Jaquemet et al , Hebshi et al , Goyert et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, pelagic species such as tropicbirds, noddies and terns display different foraging modes. White‐tailed tropicbirds mainly forage solitary (Jaquemet et al , Campos et al ), and occasionally associate with feeding dolphins (Jaquemet et al , Spear and Ainley ). Comparatively, sooty terns, brown and black noddies are highly gregarious and are often found in multi‐specific feeding assemblages (Evans , Au and Pitman , Jaquemet et al , Hebshi et al , Goyert et al ).…”
Section: Discussionmentioning
confidence: 99%
“…None of the tracked birds crossed the equator and reached the southern Atlantic Ocean. Campos, Andrade, Bertrand, and Efe (2018) and Santos, Campos, and Efe (2019) tracked the movement of white‐tailed tropicbirds ( P. l. ascensionis ) during chick‐rearing from Fernando de Noronha archipelago and showed that long foraging trips reached an average distance from the breeding colony of 105 ± 48 km. This reinforces the hypothesis of a lack of connectivity between northern and southern populations of the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…Ecologically, they share with boobies, gannets and terns the ability of plunge diving, but unlike these species, they avoid foraging in large multi-species flocks (Spear & Ainley, 2005). They are also unusual in that although they fly long distances (comparable to procellariids), they lack the ability to soar (Spear & Ainley, 1997; Mannocci et al, 2014; Campos et al, 2018). This flight behaviour seems to be possible because they rest for long periods on the water between periods of flight (Spear & Ainley, 2005; Mejias et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This flight behaviour seems to be possible because they rest for long periods on the water between periods of flight (Spear & Ainley, 2005; Mejias et al, 2017). Despite these unusual characteristics, tropicbirds have only been tracked in a few studies (Pennycuick et al, 1990; Le Corre et al, 2012; Soanes et al, 2016; Mejias et al, 2017; Campos et al, 2018), which greatly limits our understanding of their foraging ecology.…”
Section: Introductionmentioning
confidence: 99%